The Correlation between Post-Abortion Grief and Quality of Life in Females With a History of Abortion Visiting Health Centers and Hospitals of Shahid Beheshti University of Medical Sciences, Iran During Year 2016 - Feizollahi, Narjes; Nahidi, Fatemeh; Sereshti, Manije; Nasiri, Maliheh (Advances in Nursing & Midwifery, 2018)
Background: Grief is a common reaction pf parents to abortion. It may be followed by various psychological complications that affect women's individual-social quality of life. This study aimed to determine the correlation between post-abortion grief and quality of life of women with a history of abortion. Materials and Procedures: This descriptive-correlational study was conducted in 2016. Convenience sampling was applied to select 165 women with a history of abortion from health centers and hospitals affiliated to Shahid Beheshti University of Medical Sciences (Tehran, Iran). A demographic and fertility questionnaire, the Perinatal Bereavement Grief Scale, and the World Health Organization Quality of Life Questionnaire were used to collect data. Descriptive statistics and Pearson’s and Spearman’s correlation tests were administered to analyze the data. All analyses were performed using SPSS 20. Findings: There was a significant relationship between quality of life and post-abortion grief (r = -0.387; p < 0.001) and the mean score of quality of life decreased with an increase in the intensity of post-abortion grief. Women with a history of abortion had a moderate level of post-abortion grief (mean score out of 100: 47.52 ± 9.01 ) and intensity of post-abortion grief in less than 3 months from abortion occurrence until completion of the questionnaire has been at its highest level (with a mean and standard deviation of 421.3 ± 99.3) and has declined over the time. However, there was no significant relationship between the intensity of the grief and the time of abortion. and desirable quality of life (mean score: 91.90 ± 14.43). Conclusion: The findings of this study suggested an association between more severe post-abortion grief and decreased quality of life, i.e. post-abortion grief had adverse effects on women’s quality of life. Therefore, fertility health policy makers are recommended to develop appropriate measures to reduce grief and improve the quality of life of women after abortion.